Vaccine Hesitancy and Mandatory Immunizations in Emilia-Romagna Region: the case of MMR vaccine - Gori, Davide; Ialonardi, Magda; Odone, Anna; Ricci, Beatrice; Pascucci, Maria Grazia; Frasca, Gabriella; Venturi, Sergio; Signorelli, Carlo; Fantini, Maria Pia (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: An increase of vaccine hesitancy has spread worldwide and lead to reduction in coverage rates. The trivalent Measles-Mumps-Rubella (MMR) vaccine has been one of the most targeted leading due to possible (but never proven) adverse effects. This resulted in an increase of measles cases. The aim of the study is to analyze the 24-months coverage rates for the MMR vaccine in Emilia-Romagna Region (RER) between 2007 and 2018 and to correlate any significant changes to index events. Methods: Official aggregate data on vaccination coverage at 24-month provided by the RER and the Italian Ministry of health were analyzed and discussed. Results: From 2012 to 2015 a significant reduction in vaccination rates has been registered. In the following years an increase was recorded temporarily related to national and regional laws. Conclusion: The mandatory vaccination strategies seem to be in the short period effective in RER to counteract the growing population neegative attitudes towards vaccination and mitigate vaccine hesitancy.